How do you simplify #-9(x/3)^2#?

1 Answer
Feb 11, 2017

Answer:

See the entire simplification process below:

Explanation:

First, we will use these two rules of exponents to simplify the terms within parenthesis:

#a = a^color(red)(1)#

#(x^color(red)(a))^color(blue)(b) = x^(color(red)(a) xx color(blue)(b))#

#-9(x/2)^2 = -9(x^color(red)(1)/3^color(red)(1))^color(blue)(2) = -9(x^(color(red)(1) xx color(blue)(2))/(3^(color(red)(1) xx color(blue)(2)))) = -9(x^2/3^2) =#

#-9(x^2/9) = -color(red)(cancel(color(black)(9)))(x^2/color(red)(cancel(color(black)(9)))) = -x^2#